Ответы и объяснения

2014-01-11T19:43:40+00:00
(- \frac{1}{8}  ) ^{-2}  - 0,01 ^{-1} =
=(- \frac{8}{1} )^{2} - ( \frac{1}{100} ) ^{-1} =
=(-8) ^{2} - ( \frac{100}{1} )^{1} =
=64-100=-36

(- \frac{1}{6} ) ^{-3} * (- \frac{1}{6} )=(- \frac{1}{6} )^{-3+1} =
=(- \frac{1}{6} ) ^{-2} = (- \frac{6}{1} ) ^{2} = 36

( \frac{2}{15} )^{-11} : ( \frac{2}{15} )^{-10}  = ( \frac{2}{15} )^{-11 - (-10)} =
=( \frac{2}{15} )^{-1}  = ( \frac{15}{2} )^{1}  =  \frac{15}{2} = 7,5
привет реши если сможешь реши пару примеров у меня